1990
DOI: 10.1165/ajrcmb/2.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Cell Kinetics of Normal Adult Hamster Bronchial Epithelium in the Steady State

Abstract: To establish the progenitor role of bronchial epithelial cells in the steady state, we undertook a quantitative autoradiographic study in normal hamsters. Groups of 7 hamsters were killed 1 h and 1, 2, 3, 4, 7, and 14 d after an intraperitoneal injection of [3H]thymidine (2 microCi/g body wt). Autoradiograms were prepared from 861 Epon sections, 2 microns thick, of left intrapulmonary hilar bronchi. Epithelial cells were classified into 1 of 7 categories: basal-1 (B1) and basal-2 (B2), depending on nuclear hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 21 publications
3
43
0
1
Order By: Relevance
“…There is differential expression of these proteins in airway BCs. At steady state, most mouse tracheal BCs express KRT5, whereas only a subset expresses KRT14 [82]. Mouse BCs generated lineage-labeled basal, ciliated and Clara cells [15].…”
Section: Goblet Cell Differentiation and Hyperplasia From Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…There is differential expression of these proteins in airway BCs. At steady state, most mouse tracheal BCs express KRT5, whereas only a subset expresses KRT14 [82]. Mouse BCs generated lineage-labeled basal, ciliated and Clara cells [15].…”
Section: Goblet Cell Differentiation and Hyperplasia From Stem Cellmentioning
confidence: 99%
“…By contrast, lineagelabeledClara cells expressing SCGB1A1 + cellsin the trachea proliferate and generate ciliated cells but a population was replaced over time by unlabeled progenitor cells, presumably BCs [12]. This suggests that, in airway epithelia containing BCs, the Clara cells do not function as stem cells over the long term under normal conditions.On the other hand, Randell [80] reviewed that both BCs and nonciliated columnar epithelial cells of the rodent trachea proliferate in the steady state and in response to injury [81,82]. BCs can regenerate a fully differentiated mucociliary epithelium when seeded in denuded tracheas (host tracheas that have been stripped of their epithelium) and transplanted subcutaneously in nude rats [83,84].…”
Section: Goblet Cell Differentiation and Hyperplasia From Stem Cellmentioning
confidence: 99%
“…In the 1960s, Blenkinsopp examined the available data in lung and also performed experiments in rats, indicating a relatively slow epithelial cell turnover, estimated to be approximately 100 d in the normal rodent tracheobronchial tree (14). Numerous studies since then have confirmed relatively slow rates of cell turnover in normal lungs, but proliferation was highly induced after injury (15)(16)(17)(18)(19)(20).…”
Section: Models Of Cell Replacement and Applicability To The Lungsmentioning
confidence: 99%
“…Both basal and nonciliated se-cretory cell types of bronchial airways have been shown to exhibit proliferative capacity. 8,9,11,12,20,21,47 However, the relative contribution of secretory versus basal progenitor cell populations to epithelial maintenance and regeneration following injury remains controversial. Studies by Evans and colleagues 12 involving injury targeted to ciliated cells indicated that nonciliated secretory cells represent the preferred progenitor cell type of the bronchial epithelium.…”
mentioning
confidence: 99%